China's growth the making of an economic superpower - Yueh, Linda Y. (Linda Yi-Chuang) (Oxford University Press, 2013)
"China's economic growth has transformed the country from one of the poorest in the world to its second largest economy. Understanding the drivers of growth remains elusive as the country is affected by both its transition from central planning and the challenges of a developing country. This book examines the main themes of growth, offering micro level evidence to shed light on the macro drivers of the economy. It also focuses on law and informal institutions of the economy to highlight the importance of entrepreneurship and the development of the private sector." -- Publisher's description.